Measurement error model for the Norwegian common minke whale (Balaenoptera acutorostrata acutorostrata) surveys 2008-2013 - Solvang, Hiroko K.; Skaug, Hans J.; Øien, Nils (J. Cetacean Res. Manage., 2021)
A discrete measurement error model for radial distance and angle to detected objects in line transect surveys is considered. This approach directly quantifies the effect of measurement error on the estimated effective strip half-width. We apply the method to experimental data collected over the period 2008-2013 in North Atlantic both under the assumption of multiplicative and additive measurement errors. Our results indicate that the abundance estimates considering the measurement error are consistently larger than the abundance estimates without any measurement error correction.